A Paradigm of Monks Management for Development of Highland Community in Kanlayaniwatthana District, Chiang Mai Province - Pornthin, Prasert (Journal of International Buddhist Studies, 2023)
The purposes of this research were 1) to study the principles of monk’s management for development of highland community, 2) to study the model of monk’s management for development of highland community, and 3) to suggest the appropriate management model for development of highland community. The results of research were as follows: For administrative Aspect, it was found that In each community, there is one monk or novice together with few temple boys living in the Ashram. The monk or novice attends the meeting with villagers. There are the Buddhist leaders in some communities. The Ashrams are distributed in every district. The head of highland moral propagation center has responsibility for superintending and supervising monks and novices, he only follows the policy of the Phradhammajarika project, and has no authority to give benefit or punishment to monks or novices, and to make a decision in transferring them. For Religious Study Aspect, it was found that there are no teaching and learning of Phrapariyatthidhamma in Kanlayaniwatthana District, because most of monks or novices working in this area have already graduated with Nakdhamma and they just wanted to work, they temporarily. Moreover, it is because of the newly established district. Therefore the lack of Dharma and Pali teaching and learning is the weak point of religion propagation in this District. Special Education Aspect, it was found that in some communities, there is a Buddhist Sunday School for student of primary and secondary educational levels while there is no such school in some communities, because the monks or novices in those areas are not ready to import Buddhist leaching to the young people. Propagation of Religion Aspect, it was found that monks or novices teach Buddhist principles to villagers on national important days and Buddhist important through community radio broadcasting stations. They also encourage young people to profess regarding Buddhism. Public Assistance Aspect, it revealed that monks or novices help people to seek fund for infrastructure project in community from regional office of Phradhammajarika. They not only seek the source of fund, but also plant around Ashram area which is a good example for villagers. A lack of budget and building instruments causes the inconvenience to the villagers in doing different activities. For Public Services Aspect, it was found that monks and novices working in communities have given help to the people who face problems and have less educational opportunity both individually and in group and they also help community people by giving them advice. The Buddhist monks have played important roles in working work community people by establishing different groups of the aged and farmers and by organizing various community development projects and these projects were forwarded to the organizations at local or the regional office of Phradhammajarika Project.